The Genome Sequence of Bluetongue Virus Type 10 from India: Evidence for Circulation of a Western Topotype Vaccine Strain - Maan, Sushila (American Society for Microbiology, 2012)
Bluetongue virus is the type species of the genus Orbivirus in the family Reoviridae. We report the first complete genome sequence of an isolate (IND2004/01) of bluetongue virus serotype 10 (BTV-10) from Andhra Pradesh, India. This isolate, which is stored in the Orbivirus Reference Collection (ORC) at IAH Pirbright, shows >99% nucleotide identity in all 10 genome segments with a vaccine strain of BTV-10 from the United States.